Physicochemical and fourier transform infrared spectroscopic analysis of Bika (Ampelossus martini Planch.) and grape (Vitis vinifera) seed oils. - Osunero, April Joyce Sumugat
The demand for seed oils is now increasing due to its nutritional value. On of the economically important seed oil is the grape (Vitis vinifera) seed oil. The characteristics of bika (Ampelocissus martini Planch.) seed oil were identified to determine if it could be an alternative to the expensive grape seed oil. Grape seed oil and bika seed oil were extracted using hexane. The total crude fat of grape seed oil and bika seed oil were 8.76 percent and 12.22 percent respectively. Iodine value is higher in grape seed oil (152.87 I2/100 g oil) than in bika seed oil(126.70 I2/100 g oil) , as well as specific gravity which is 0.92009 for grape seed and 0.8987 for bika seed. Acid value is lower in grape seed oil (0.2621 g acid/oil) than in bika seed oil (15.71 g acid/ oil), and also in saponification number which is 226.04 g KOH/g oil for grape seed oil and 233.05 g KOH/g oil for bika seed oil. The refractive index for grape seed oil and bika seed oil are 1.476 and 1.466, respectively. There is no significant difference in the saponification value; however there is significant difference in the crude fat, iodne value and acid value. The FTIR spectra showed that grape seed oil and bika seed oil is almost identical and varies only in the presence of acidic component and probably the proportion of unsataturated and saturated fatty acid.